Per os infectivity of white spot syndrome virus (WSSV) in white-legged shrimp (Litopenaeus vannamei) and role of peritrophic membrane. (December 2016) - Thuong, Khuong; Tuan, Vo; Li, Wenfeng; Sorgeloos, Patrick; Bossier, Peter; Nauwynck, Hans
Abstract As earlier observations on peroral infectivity of WSSV in white-legged shrimp are conflicting, here, a standardized peroral intubation technique was used to examine (i) the role of the physical composition of the viral inoculum and (ii) the barrier function of the PM. In a first experiment, the infectivity of a WSSV stock was compared by determining the SID50 by intramuscular injection, peroral inoculation or via feeding. The following titers were obtained: 108.77 SID50 /g by intramuscular injection, 101.23 SID50 /g by peroral inoculation and 100.73 SID50 /g by feeding. These results demonstrated that 107.54 –108.03 infectious virus is needed to infect shrimp by peroral inoculation and via feeding. Next, it was examined if damage of the PM may increase the susceptibility for WSSV by peroral route. The infectivity of a virus stock was tested upon peroral inoculation of shrimp with and without removal of the PM and compared with the infectivity upon intramuscular inoculation. The virus titers obtained upon intramuscular injection and peroral inoculation of shrimp with and without PM were 108.63, 101.13 and 101.53 SID50 /mL, respectively. This experiment confirmed the need of 107.1 –107.5 infectious virus to infect shrimp via peroral route and showed that the removal of the PM slightly but not significantly (p  > 0.05) facilitated the infection of shrimp. This study indicated that WSSV contaminated feed is poorly infectious via peroral route, whereas it is highly infectious when injected into shrimp. The PM plays a minor role as internal barrier of shrimp against WSSV infection.